STRATEGI GURU PAUD MEMANFAATKAN BUKU CERITA INTERAKTIF UNTUK MENUMBUHKAN MINAT BACA ANAK USIA 5-6 TAHUN (System Riview Literature) - Lina Amelia; Ridhatul Lisfa; Leli Hasanah; Faza Nujjiya; Radhiyatul Muna (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
Early childhood reading interest is an important foundation for sustainable language, cognitive, and literacy development. Although various studies have demonstrated the effectiveness of interactive storybooks in supporting children's literacy development, studies specifically synthesizing teacher strategies in utilizing this medium are still limited. This study aims to analyze the strategies of early childhood education (PAUD) teachers in using interactive storybooks to increase reading interest in children aged 5–6 years. The study used the Systematic Literature Review (SLR) method by reviewing 12 national scientific articles published between 2022 and 2026. These articles were obtained through a process of identification, selection, and evaluation based on predetermined inclusion and exclusion criteria. The study results indicate that teacher strategies consist of three main stages: pre-reading through the picture walk technique, while reading using dialogic reading, and post-reading through story retelling activities. These strategies have been shown to improve vocabulary, narrative comprehension, listening skills, and reading motivation in early childhood. Furthermore, collaboration between teachers, parents, and schools plays a crucial role in strengthening the success of literacy programs. Research findings indicate that the effectiveness of interactive storybooks is determined not only by their visual, audio, and interactive features, but also by the teacher's ability to implement targeted learning strategies that are appropriate to the child's developmental characteristics. Therefore, strengthening teacher competency and developing family literacy programs are crucial factors in optimizing the use of interactive storybooks in early childhood education (PAUD).